2010
DOI: 10.1080/09603101003652417
|View full text |Cite
|
Sign up to set email alerts
|

An application of closed-form GARCH option-pricing model on FTSE 100 option and volatility

Abstract: Many researches indicate that the Black-Scholes (BS) option-pricing model demonstrates systematic biases due to some unreasonable assumptions. In practice, implied volatilities tend to differ across exercise prices and time to maturities. To solve the problem, Heston and Nandi (HN) (2000) develop closed-form Generalized Autoregressive Conditional Heteroscedasticity (HN-GARCH) model. In this study, we apply their model on Financial Time Stock Exchange (FTSE) 100 index option. As a benchmark, we employ the ad ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Jackwerth and Rubinstein (2001) and Li and Pearson (2007) found that the AHBS model performed better than the BSM model and other more mathematical models. Duan and Zhang (2001), Fofana and Brorsen (2001), Lehar et al (2002), Sabbatini and Linton (2004), Bollen and Rasiel (2003), Su et al (2010) all found empirical evidence about the superiority of the GARCH option-pricing model as compared to the BSM and AHBS models, but this was contradicted by Harikumar et al (2004). Bakshi et al (1997) found the pricing and hedging performance of stochastic volatility models to be much better than that of the BSM model, which was confirmed by Kim and Kim (2003), Dupoyet (2006) and Moyaert and Petitijean (2011).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Jackwerth and Rubinstein (2001) and Li and Pearson (2007) found that the AHBS model performed better than the BSM model and other more mathematical models. Duan and Zhang (2001), Fofana and Brorsen (2001), Lehar et al (2002), Sabbatini and Linton (2004), Bollen and Rasiel (2003), Su et al (2010) all found empirical evidence about the superiority of the GARCH option-pricing model as compared to the BSM and AHBS models, but this was contradicted by Harikumar et al (2004). Bakshi et al (1997) found the pricing and hedging performance of stochastic volatility models to be much better than that of the BSM model, which was confirmed by Kim and Kim (2003), Dupoyet (2006) and Moyaert and Petitijean (2011).…”
Section: Literature Reviewmentioning
confidence: 88%
“…A comparing review of GARCH-M, EGARCH, TGARCH, and PGARCH is stated by a few researchers based on researchers such as (Su, 2010;Miron, Tudor, 2010;Awartani, Corradi, 2005;Gokan, 2000) that all the asymmetric models in GARCH helps to predict the volatility of daily return on stock throughout the world. Amongst all of the EGARCH models, it fits best to measure the volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, CGARCH and TGARCH are supported by Gokbulut and Pekkaya (2014) as they find them more suitable for measuring volatility. A series of analyses were conducted by researchers from emerging countries like Kumar and Mishra (2019b), Floros (2008) in Nigeria, Moustafa Abd et al (2011, Angabini andWasiuzzaman (2011) in Malaysia, Ezzat Hassan (2012) of Egypt, Su (2010) in China, Emenike (2010) andFreddie et al (2012) of Saudi Arabia who made a comparison of various models from the GARCH and ARCH family and concluded that GARCH, GJR GARCH, and EGARCH are fitting for the clustering effect, leptokurtosis volatility measurements, and identifying leverage effect. Kumar and Biswal (2019) attempted a study to measure the volatility clustering and leverage effect of top future stock markets from Jan 1st, 2014, to Oct 31st, 2018, by implementing the GARCH family model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the work of Engle (1982) and Bollerslev (1986), a number of papers have been published to investigate the performance of the volatility models (see, e.g. Christoffersen and Jacobs, 2004b;Su et al, 2010;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%